The Implementation of the CoreTax System to Improve the Performance of Withholding Tax Certificate (Bupot) Preparation for Article 21 Income Tax: A Qualitative Approach - Atha Farras; Kristina Ika Muliawati; Vinka Yuliana; Nofryanti Nofryanti (The Future of Education Journal, 2025)
The implementation of the Core Tax Administration System (CTAS), also known as CoreTax, represents a strategic initiative by the Directorate General of Taxes to carry out the digital transformation of tax administration in order to improve the national tax ratio. This study aims to analyze the benefits, advantages, and challenges in the implementation of the CoreTax system, particularly with regard to the operational effectiveness of issuing Withholding Tax Certificates (Bukti Potong/Bupot) for Article 21 Income Tax. The research employed a descriptive qualitative method with a case study approach conducted at a Tax Consulting Office in South Tangerang, where data were collected through direct observation and structured interviews with five tax consultant staff members. The findings indicate that CoreTax significantly enhances performance by strengthening Perceived Ease of Use (PEOU) after the initial adaptation phase, supported by automated data input features such as XML import and pre-populated data that effectively mitigate the risk of human error. The integration of multiple modules within a single platform also provides a digital audit trail that supports transparency and reporting time efficiency. However, field findings reveal that the efficiency benefits of CoreTax remain conditional due to infrastructure constraints, particularly server instability (downtime and query timeouts) during peak reporting periods. Therefore, strengthening technological infrastructure, optimizing cloud scaling, and providing offline draft features are necessary to maintain platform reliability and to support sustainable taxpayer compliance.